Nanomaterial modified electrodes : optimization of voltammetric sensors for pharmaceutical and industrial application - Brimecombe, Rory Dennis (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
Nanomaterials, in particular carbon nanotubes have been shown to exhibit favourable properties for the enhancement of electrochemical detection of target analytes in complex matrices. There is however scope for improvement in terms of the optimization thereof in electrochemical sensors surface modification. The aim of this thesis was to examine methods that would result in increased current response, lowered passivation and application of such modified surfaces with application to pharmaceutically and industrially relevant analytes. Current methods for enhancing the performance of carbon nanotubes include acid functionalization which not only increases the hydrophilicity of the nanotubes, and consequently their ability to provide stable (aqueous) suspensions, but also introduces electrochemically active sites. This particular approach is however not normalized in the literature. Over-exposure to acid treatment results in loss of structural integrity of the carbon nanotubes, and as such a fine balance exists between achieving these dual outcomes. Guided by high resolution scanning electron microscopy, atomic force microscopy, voltammetric and impedance studies, this thesis examined the role of the length of time of the acid functionalization process as well as the impact of activation of carbon nanotubes and fullerenes on electrochemical sensor performance. Based on desired charge transfer resistances, rate transfer coefficients and sensitivity towards redox probes the optimal length of acid functionalization for multiwalled carbon nanotubes was 9 hours and 4 hours for single-walled carbon nanotubes. Further improvements in the desired outcomes were achieved through electrochemical activation of the modified electrode surface by cycling in the presence of catechol, in a novel approach. By employing electrochemical impedance spectroscopy it was observed that catechol activation resulted in lowered charge transfer resistance, before and after activation, with functionalized multi-walled carbon nanotubes (9 hours) exhibiting the greatest decrease of 90 % and functionalized single-walled carbon nanotubes (4 hours), a 50 % decrease. Corresponding increases in the heterologous rate transfer coefficient showed a 770 % increase for functionalized multi-walled carbon nanotubes (9 hours), following catechol activation. Comparative observations for fullerenes following partial reduction in potassium hydroxide yielded a 30 % decrease in charge transfer resistance, with an increased heterologous rate transfer coefficient at a fullerene modified surface The performance of the nanomaterial modified electrodes was applied to the detection of wortmannin with applications in bioprocess control and in the pharmaceutical sector as well as to the detection and monitoring of the industrial dye Reactive red. Of particular relevance to these analytes was the assessment of the nanomaterial modified electrodes for enhanced stability, reproducibility, sensitivity and decreased passivation effects. In this study the first known account of wortmannin detection through electrochemical methods is reported. Voltammetric characterization of wortmannin revealed an irreversible cathodic process with a total number of 4 electrons and a diffusion coefficient of 1.19 x 10-7 cmÂ².sâ »Â¹. At a functionalized multiwalled carbon nanotubes modified glassy carbon electrode a limit of detection of 0.128 nmol.cmâ »Â³ was obtained, and with limited surface passivation the detection scheme afforded pertinent analyses in biological media representing a substantial improvement over chromatographic detection methods. This study also provided the first account of the voltammetric detection of reactive red, competing favourably with traditional spectroscopic methods for monitoring biodegradation of this compound in real time.
Keywords: Voltammetry; Electrochemistry; Nanotubes; Nanostructured materials